APPLICATION OF THE POLITICAL PARTY INFORMATION SYSTEM (SIPOL) IN IMPROVING THE QUALITY OF THE ELECTION PARTICIPANT SELECTION PROCESS IN THE TEGAL CITY KPU - Dwi Pratiwi, Dita; Sutjiatmi, Sri; Setio Widodo, Agus; Ayu Fadilah, Dewi; Mahadika, Alam (Universitas Pancasakti Tegal, 2023)
General elections are held with the intention of electing community representatives who can then form a government, continue the independence movement, and uphold the integrity of the Unitary State of the Republic of Indonesia. Political parties themselves are a forum for association and gathering of people to participate in government guaranteed by the constitution. In becoming election participants political parties and members of political parties must register through the Political Party Information System (SIPOL) created by the election organizers, namely the General Election Commission in order to help make it easier for political parties to register and assist the KPU in carrying out the stages of verification and determination of political parties participating in elections as well as creating more transparent and accountable parties and increasing orderliness of political parties in the registration stage. The purpose of this research is to describe the application of political party information systems, especially in Tegal City, as well as to describe the quality of political parties. This study uses a qualitative descriptive research method, with data analysis techniques using Nvivo analysis to obtain systematic analysis results. The results of the study show that the application of the Political Party Information System at the Tegal City KPU and the Tegal City political parties is said to be quite good. Where from the KPU and political parties they feel very facilitated by the existence of SIPOL as a tool for registering, verifying, and determining political parties participating in elections, as well as the level of transparency and accountability of political parties has increased since the existence of SIPOL